STRATEGI BERTAHAN HIDUP PEREMPUAN KEPALA KELUARGA - Yudithia Himawati; Budi Muhamad Taftazani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Female headed households are faced with various challenges and obstacles during their lives including multiple roles, discrimination, and economic difficulties which require them to develop strategies to survive. This study aims to describe the survival strategies of female headed households using library research methods. The survival strategy is examined through three aspects, namely the active strategy carried out by maximizing existing potential such as prioritizing energy, skills, talents and knowledge to meet family needs. Then, the passive strategy is to reduce the cost of living for the family by helping each other, in debt, and being creative. Furthermore, the network strategy carried out by women heads of households is to utilize networks between individuals, kinship, communities, groups, government and even outsiders who have concern for the welfare of female headed households. Thus, this study seeks to identify various survival strategies adopted by female headed households with their underlying dynamics. The network strategy is seen as being able to support female headed households to develop their active and passive strategies